The Impact of Islamic Human Development Index and Fiscal Decentralization on Poverty Levels in North Sumatra - Harun, Ahmad; Zakik, Zakik; Kurniasari, Widita (MediaTrend, 2025)
This study aims to analyze the influence of the Islamic Human Development Index (IHDI) and Fiscal Decentralization on Poverty Levels in Districts/Cities in North Sumatra Province during 2016-2022. The research method uses explanatory research with quantitative data to estimate the influence of dependent variables (IHDI and Fiscal Decentralization) on the Poverty variable. The calculation of the IHDI variable uses the theory and model of Maqashid Syari'ah. The results of this study include is the Islamic Human Development Index (IHDI) has a negative and significant effect on poverty at a 95 percent confidence level in districts/cities in North Sumatra province during 2016-2022. Government spending in the education and health sectors has a negative and significant effect at the 95 percent confidence level. In comparison, government spending in the social sector has a negative but not significant effect at the 95 percent confidence level on poverty in districts/cities in North Sumatra province during 2016-2022. 3). The magnitude of the influence between all variables used, namely; Islamic Human Development Index (IHDI), government spending on education, government spending on health and government spending on social issues on poverty, is 92.78 percent and the remaining 8.22 percent is influenced by other variables that are not analyzed in this study.